Html, css, and javascript mobile development for dummies ebook - Harrel, William (Dummies., 2011)
Learn to build and optimize attractive, functional web sites for smartphones Today, mobile devices outnumber desktop and laptop computers three to one. Skill in developing web sites that work on mobile devices is in demand, and this friendly, step-by-step guide shows how to build and optimize sites using HTML5 and other standard web development tools. Building web sites that work for all types of smartphones and tablets, including iPhones, iPads, Android devices, and BlackBerry devices is a skill much in demand as mobile devices outpace both desktop and laptop computers, and this book gets you started. Guides you through creating and optimizing mobile sites with HTML, CSS, and JavaScript Covers HTML5, WebKit extensions, platform variations, accommodating different browsers, security issues, and making mobile sites richer with Flash, graphics, and video Includes code for differences in mobile app design and navigation, including touch devices HTML, CSS, and JavaScript Mobile Web Development For Dummies makes it easy to start developing great sites for mobile devices.